2022
DOI: 10.1021/acsnano.2c03781
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Nanovesicles Convert the Skeletal Endothelium-Associated Secretory Phenotype to Treat Osteoporosis

Abstract: Recently, bone marrow endothelial cells (BMECs) were found to play an important role in regulating bone homeostasis. However, few studies utilized BMECs to treat bone metabolic diseases including osteoporosis. Here, we reported bioinspired nanovesicles (BNVs) prepared from human induced pluripotent stem cells-derived endothelial cells under hypoxia culture through an extrusion approach. Abundant membrane C-X-C motif chemokine receptor 4 conferred these BNVs bone-targeting ability and the endothelial homology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 60 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…In addition, bone-targeting molecules could also be coupled with nanomaterials to increase their skeletal accumulation. Bioinspired exosomes or nanovesicles have been fabricated with abundant bone-targeting molecules present on their surface, showing 2–10 times more accumulation in the bone (mainly femur) compared to plain nanovesicles ( Cui et al, 2022a ; Cui et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bone-targeting molecules could also be coupled with nanomaterials to increase their skeletal accumulation. Bioinspired exosomes or nanovesicles have been fabricated with abundant bone-targeting molecules present on their surface, showing 2–10 times more accumulation in the bone (mainly femur) compared to plain nanovesicles ( Cui et al, 2022a ; Cui et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bioinspired nanovesicles from human induced pluripotent stem cell-derived endothelial cells were engineered to secret cytokines, favoring osteogenesis and anti-inflammation. It induced the osteogenic differentiation of the bone mesenchymal stem cells (BMSCs) and the M1-macrophage-dominant pro-inflammatory microenvironment in the osteoporotic bones in ovariectomized mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, physical manipulation is performed by directly exerting physical forces on the parent cells by electroporation and extrusion ( Richter et al, 2021 ), thereby optimizing EVs derived from them. Cui et al (2022) reported bioinspired nanovesicles prepared from human iPSC-derived endothelial cells under hypoxia culture through an extrusion approach. Abundant membrane C-X-C motif chemokine receptor 4 conferred these nanovesicles bone-targeting ability and the endothelial homology facilitated the bone marrow endothelial cells tropism.…”
Section: Application Of Engineering Modified Extracellular Vesicles I...mentioning
confidence: 99%